Metabolic variations biological evaluation of Clinacanthus in nutans (Burm. f.) lindau leaf extracts on lipopolysaccharides-induced neuroinflammation in rats - Ahmad Azam, Amalina (2020)
Neuroinflammation is a complex response of injury on any part of the brain resulted in the activation of glial cells, release of inflammatory mediators like cytokines and chemokines, reactive oxygen and nitrogen species, which is a pathological hallmark of many neurological disorders. Therefore, effective control of neuroinflammation is crucial to prevent the related diseases. In this study, the matured leaves of 9-week old Clinacanthus nutans (Burm. f.) Lindau (CN) extracted with water and two ethanolic (50% and 100%) phytochemical constituents were profiled by using proton Nuclear Magnetic Resonance (1H NMR) metabolomics approach. The highest nitric oxide (NO) inhibitory activity, in the in vitro neuroinflammation model using the lipopolysaccharides (LPS)- induced BV2 cell line, was observed for aqueous extract with an IC50 value of 336.2 ± 4.7 μg/ml. Correlation between NO inhibitory activity and CN constituents by partial least square (PLS) analysis resulted in the identification of most potential metabolites responsible for the activity being schaftoside, acetate, propionate, alanine, and Clinacoside C. The in vivo model of neuroinflammed Sprague Dawley rats induced with LPS was also done via the metabolomics approach. The findings from multivariate data analysis (MVDA) highlighted several similarities and dissimilarities in metabolites concentration in LPS-induced rats (LPS+water) and LPS-induced treated with CN extracts. Although CN doses treated group did not alleviate to ascertain level of cure, continuous 14 days oral administration of aqueous CN extract at 500 (CN500) and 1000mg/kg BW (CN1000) was able to moderately ameliorated the neuroinflammation activity in a similar manner as the positive drug, dextromethorphan hydrobromide (DXM) at 5mg/kg BW. A consistent result has been observed for serum by both analytical platforms of liquid chromatography-mass (LC-MS) and NMR, the physiological sickness behavior and 1H NMR brain tissue of the neuroinflammed male rats. The alteration of lipid metabolism; (lysophosphatidic acid (LPA) and 5- diphosphomevalonic acid) in sera of multiplatform model, and the changes of metabolites in the brain tissue namely, lactate, pyruvate, phosphorylcholine, glutamine, and-ketoglutarate in CN500 and DXM exhibited an ameliorating effect when compared to the controlled neuroinflammed rats. CN treatments also significantly reduced IL-1β, a pro-inflammatory cytokine better than DXM as proven in the quantification of cytokinesby microarray analysis. The physiological sickness behavior such as anxiety, exploration and reduction of locomotion also improved by CN treatments as visualized in the principal component analysis (PCA) model. Hence, herein a comprehensive view of the CN effects in neuroinflammation caused by LPS was successfully profiled, correlated and deciphered between central neuroinflammation, systemic metabolic and physiological disturbance which has potential for future ethnopharmacological and/or nutraceutical studies.